Starting with React.js - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2017)
"Any IT professional or hobbyist anticipating a solid understanding of how React works in web and mobile solutions needs to go through this course. Anyone desiring to learn how React and Flux solutions are designed, administered, and developed needs the knowledge and practice presented in this course. This not only includes web, mobile, and service application developers, but also architects, UI designers, testers, and administrators. This course provides a solid understanding of how to get React projects up and running."--Resource description page.
Title and publication information from resource description page (Safari, viewed April 6, 2017).
Keywords: Web applications; Web applications -- Design; JavaScript (Computer program language); Application software -- Development; Electronic books